Os critérios de movimentação na carreira de professores da educação básica em estados da Região Norte do Brasil - CARNEIRO, Ana Paula da Silva (Universidade Federal do Pará, 2017)
The present dissertation deals with the configuration and criteria for the career movement of teachers of basic education in the state education network of Acre, Amapá, Rondônia and Roraima, considering the peculiar condition of these States, originally Federal Territories. Through documentary study the criteria of career movement were analyzed in order to identify possible signs of attractiveness and incentives to remain in the career of basic education. The study started with the following questions: How has the career structure in the state education network been configured in the states of Acre, Amapá, Rondônia and Roraima? What are the criteria for moving teachers' careers defined in the State Education Networks Plans of these states? Do these criteria provide attractiveness and incentives to stay in the career? When, in the Federal Territories, the career plan of basic education teachers in these places was unified and presented as the main criterion for career movement the length of service, while the qualification was considered as a secondary criterion, which corresponded to the career of the Traditional type. When the Federal Territories assumed the position of states of the federation, the career of teachers also changed, assuming signs of a professional career, in line with changes in the Brazilian legal system. The capitalist crisis and the redefinition of the state's role since the end of the last century have led to new premises for the management of the public service such as performance evaluation, meritocracy and accountability. The configuration of the career paths of these states begin to assimilate such premises. The performance evaluation takes center stage to the detriment of the time of service as a criterion for the movement in the career of the teaching profession in the states surveyed. Although the criteria for career mobility are in line with national guidelines, in a few states they are effective, which does not contribute to attractiveness and career permanence. However, there is a process of permanent struggle of the teachers in their organizations for the implementation / effectiveness of the Career Plans in the researched states, signaling that there is still much that advances towards the appreciation of the teacher.